Pendampingan Teknis Pemasangan dan Perawatan Pembangkit Listrik Tenaga Surya di Desa Tablolong Nusa Tenggara Timur - I Made Aditya Nugraha; Febi Luthfiani; Grangsang Sotyaramadhani; Muhamad Amril Idrus; Kaminton Tambunan; Marcus Samusamu (Rengganis Jurnal Pengabdian Masyarakat, 2021)
The huge potential of solar energy and the increasing demand for electrical energy when fishing at night allow fishing boats in Tablolong Village to use solar power plants as a source of electrical energy. The purpose of this utilization can indirectly overcome the need for electrical energy on fishing boats and reduce the use of fossil energy to turn on generators. Service activities in the form of solar power plants installation and maintenance training are in line with the policies of the Ministry of Marine Affairs and Fisheries Republic of Indonesia and the Ministry of Energy and Mineral Resources Republic of Indonesia to preserve the environment, especially the sea. This activity was attended by 24 shipowners and the installation of 80 Wp solar power plants was carried out on two ships three GT. Based on the results of the activity assessment indicators from the questionnaire that was tested using the Wilcoxon test, it was found that the service activities showed an increase in understanding and skills by the community in the use of solar power plants. This increase is seen from knowledge of the ship's electrical system, knowledge of the ship's electrical operating system, and the ability to repair and maintain the ship's electrical system.